Study of Cao-TiO2 Catalyst Calcination Ratios for the Synthesis of Biodiesel - Zainul Abidin, Muhammad Naqib; Nurul Fitriah Nasir (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study explores how varying CaO catalyst ratios affect the production of biodiesel and its physicochemical qualities. The study employs X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR) to characterize the catalysts, and evaluates the density, kinematic viscosity, and yield of the resulting biodiesel. The findings indicate that the biodiesel’s density (0.89 g/cm3 at 15°C and 0.90 g/cm3 at 40°C) and kinematic viscosity (3.7 mm2/s at 40°C) meet ASTM D6751 standards, but the yield is relatively low at 26%. The FTIR analysis shows significant interactions between CaO and TiO2, particularly at the 1:0.25 ratio, which shows a strong carbonate peak. SEM analysis reveals various degrees of particle agglomeration and porosity, which influences catalyst effectiveness. The study shows that optimising reaction conditions and improving catalyst formulations are essential for enhancing biodiesel yield and efficiency.